In-vitro biological activities of Au and Ag nanoparticles biosynthesized using commelina nudiflora L. aqueous extract - K., Palaniselvam (2015)
In this study, Commelina nudiflora L. aqueous extract was used as a reducing and stabilizing agent for the synthesis of metallic gold and silver nanoparticles. The physico-chemical and biological properties of the biosynthesized gold and silver nanoparticles were studied in a nanoscale regime. The synthesized gold and silver nanoparticles physico-chemical properties were characterized by various analytical techniques such as UV-VIS, FESEM, XRD and FT-IR. The synthesized gold and silver nanoparticles were monodispersed, and the controlled shapes and tuneable surface properties were proven. Also, the reaction parameters such as pH, temperature, plant extract concentration and metal ion concentration have been optimized to synthesize the specific sizes and shapes of the nanoparticles. The synthesized gold and silver nanoparticles were spherical and triangular in shapes with the size range of between 25 to 45 nm and 50 to 150 nm respectively. The EDX spectra show strong peaks of both gold and silver nanoparticles which are more than 80% in the sample. The XRD data supports the claim that synthesized gold and silver nanoparticles are crystalline in nature. The plant extract contains various phytochemical constituents such as saponins, alkaloids, flavonoids and phenolic compounds. These secondary metabolites may be responsible for the Au and Ag ions reduction and also help in the formation of the metal nanoparticles. Furthermore, the in-vitro antioxidant ability of C. nudiflora extracts was studied by DPPH and ABTS radical scavenging assays. The aqueous plant extract showed significant activity in the free radical scavenging which were 63.4 mg/GAE and 49.10 mg/g in DPPH and ABTS respectively. Furthermore, the biosynthesized gold and silver nanoparticles have shown reduction in the cell viability and increased cytotoxicity on HCT-116 colon cancer cells with IC50 concentration of 200 and 100 μg/ml. The flow cytometry experiments revealed that the gold and silver nanoparticles treated cells increased DNA fragmentation and significant changes were observed in sub G1 cell cycle phases compared with positive control. Finally, the mRNA gene expressions of HCT-116 cells were studied by RT-qPCR techniques. The pro-apoptotic genes were highly expressed in the gold nanoparticles treated HCT-116 colon cancer model. The apopototic genes such as PUMA (++), caspase-3 (+) and caspase-8 (++) were moderately expressed in the treated samples compared with cisplatin. Overall, these findings prove that the C. nudiflora extract successfully synthesize metallic gold and silver nanoparticles with controlled size and shapes and also acts as a potent anti-colon cancer drug in the near future.